Serum Response Factor Mediated Gene Activity in Physiological and Pathological Processes of Neuronal Motility - Knoll, Bernd (Frontiers in Molecular Neuroscience, 2011)
In recent years, the transcription factor SRF (serum response factor) was shown to contribute to various physiological processes linked to neuronal motility. The latter include cell migration, axon guidance and e.g. synapse function relying on cytoskeletal dynamics, neurite outgrowth, axonal and dendritic differentiation, growth cone motility and neurite branching. SRF teams up with MRTFs (myocardin related transcription factors) and TCFs (ternary complex factors) to mediate cellular actin cytoskeletal dynamics and the immediate-early gene (IEG) response, a bona fide indicator of neuronal activation. Herein, I will discuss how SRF and cofactors might modulate physiological processes of neuronal motility. Further, potential mechanisms engaged by neurite growth promoting molecules and axon guidance cues to target SRF’s transcriptional machinery in physiological neuronal motility will be presented. Of note, altered cytoskeletal dynamics and rapid initiation of an IEG response are a hallmark of injured neurons in various neurological disorders. Thus, SRF and its MRTF and TCF cofactors might emerge as a novel trio modulating peripheral and central axon regeneration.